Prevalência de sobrepeso/obesidade aos seis anos de idade e associação com os fatores socioeconômicos, genéticos e ambientais - Portela, Daniel Sales (2013)
Cohort study follow 672 couple of mothers and children since birth to 72 months of life. The objectives was identify economic, genetic and environment risk factors that are associated with overweight and obesity children at six years old. The research included all the children that birth in each from 10 hospitals of the city at 2004 year. The maternal hospital was visited a long period of two consecutive months, accord draw. Stander Inquiries was done after signing an informed consent. The classification to nutrition child was determinate from z-score of BMI graphics, have defined overweight/obesity that BMI ≥ +1 z-score. Stratified hierarchical statistical analysis, qui-quadratic test, p value, was considered significant values equivalent or minor of 5% with confidence interval (CI) of 95%. Logistic multivariate regression followed hierarchical levels. Overweight and obesity prevalence was 15,6% and 12,9% respective. The regress logistic analyses evidenced factors associated with final predictor maternal obesity for breastfeeding group. Children not breastfeeding had predictors as maternal obesity, father obesity, mother instruction level and cesarean delivery at the end of analysis. This study confirms the interaction of several factors to overweight and obesity, with genetics and environments factors. Early factors in the life were strongly with obesity than the neonatal predictors. There is important in the prevention of the obesity, modifier risk factors like breastfeeding practice and natural delivery. More research needs to investigate the association between cesarean delivery and excess BMI.